2014
DOI: 10.1128/aac.01515-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Danoprevir-Ritonavir plus Peginterferon Alfa-2a–Ribavirin in Hepatitis C Virus Genotype 1 Prior Null Responders

Abstract: f ; Genentech, South San Francisco, California, USA g Danoprevir (DNV) is a hepatitis C virus (HCV) protease inhibitor that achieves high sustained virologic response (SVR) rates in combination with peginterferon alfa-2a-ribavirin in treatment-naive HCV genotype 1 (G1)-infected patients. This study explored the efficacy and safety of ritonavir-boosted DNV (DNVr) plus peginterferon alfa-2a-ribavirin in G1-infected prior peginterferon-ribavirin null responders. Null responders (<2-log 10 reduction in HCV RNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This observation is in line with prior studies in which MCB was well tolerated as a component of triple or quadruple therapy regimens including peginterferon alfa/ribavirin and/or danoprevir/r [ 18 , 22 , 23 ]. Consistent with the more favorable tolerability profile of danoprevir/r compared with first-generation protease inhibitors [ 35 ], serious adverse events and withdrawals due to adverse events were more common in the present studies than reported for MCB in combination with danoprevir/r and peginterferon alfa/ribavirin [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
“…This observation is in line with prior studies in which MCB was well tolerated as a component of triple or quadruple therapy regimens including peginterferon alfa/ribavirin and/or danoprevir/r [ 18 , 22 , 23 ]. Consistent with the more favorable tolerability profile of danoprevir/r compared with first-generation protease inhibitors [ 35 ], serious adverse events and withdrawals due to adverse events were more common in the present studies than reported for MCB in combination with danoprevir/r and peginterferon alfa/ribavirin [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
“…In null responders receiving the same combination for 12 weeks, 25% (2 of 8) of those with subtype 1a and 88% (14 of 16) of those with subtype 1b HCV infections achieved SVR. 55 With vaniprevir (a drug that will be commercialized only in Japan) the rates of SVR in treatment-experienced patients without cirrhosis, infected with HCV genotype 1, were 67% (26 of 39) and 78% (91 of 117) with 300 or 600 mg twice daily, respectively, vs 19% (8 of 42) in the control group. 56 Among patients with cirrhosis, rates of SVR were 53% (8 of 15) and 68% (28 of 41), respectively, vs 14% in the control group (2 of 14).…”
Section: Available Strategiesmentioning
confidence: 99%
“… 33 Among these studies, the approved danoprevir-based regimen (danoprevir 100 mg twice daily (BID) plus ritonavir 100 mg twice daily; peginterferon alpha-2a 180 μg once weekly; and ribavirin 1000 mg/day for bodyweight <75 kg, 1200 mg/day for ≥75 kg, twice daily for 12 weeks) in treatment-naïve non-cirrhotic patients was evaluated by the MANASA study, 26 the MAKALU study, 29 the DAUPHINE study, 28 and a phase 1 study (NCT01185860). 33 …”
Section: Clinical Efficacymentioning
confidence: 99%